Evanescent waves modulate energy efficiency of photocatalysis within TiO2 coated optical fibers illuminated using LEDs - Yinghao Song (Nature Portfolio, 2021)
Coupling photocatalyst-coated optical fibers (P-OFs) with LEDs shows potential in environmental applications. Here the authors report a strategy to maximize P-OF light usage and simultaneously establish a new platform to quantify photocatalytic performance.